2005
DOI: 10.2337/diabetes.54.12.3530
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Temporal Pattern of Diet-Induced Insulin Resistance in Individual Organs and Cardiac Dysfunction in c57bl/6 Mice

Abstract: Type 2 diabetes is a heterogeneous disease characterized by insulin resistance and altered glucose and lipid metabolism in multiple organs. To understand the complex series of events that occur during the development of obesityassociated diabetes, we examined the temporal pattern of changes in insulin action and glucose metabolism in individual organs during chronic high-fat feeding in C57BL/6 mice. Insulin-stimulated cardiac glucose metabolism was significantly reduced after 1.5 weeks of high-fat feeding, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
206
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(238 citation statements)
references
References 59 publications
(57 reference statements)
27
206
4
Order By: Relevance
“…This finding stimulated us to measure tissue-specific insulin action and we showed that liver and adipose tissue exhibit peak insulin resistance for glucose metabolism within 1 week on an HFD, while additional time is required for insulin action to deteriorate in muscle. Other rodent studies using HFDs with differing lipid content and composition have reported a similar temporal pattern of the development of tissue-specific insulin resistance [7,19,20], indicating that insulin-regulated glucose metabolism in liver and adipose tissue are particularly sensitive to the effects of dietary lipid overload. However, unlike these studies we provide novel evidence demonstrating that once tissue insulin resistance develops it reaches a plateau and is not exacerbated by extended periods of fat feeding.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This finding stimulated us to measure tissue-specific insulin action and we showed that liver and adipose tissue exhibit peak insulin resistance for glucose metabolism within 1 week on an HFD, while additional time is required for insulin action to deteriorate in muscle. Other rodent studies using HFDs with differing lipid content and composition have reported a similar temporal pattern of the development of tissue-specific insulin resistance [7,19,20], indicating that insulin-regulated glucose metabolism in liver and adipose tissue are particularly sensitive to the effects of dietary lipid overload. However, unlike these studies we provide novel evidence demonstrating that once tissue insulin resistance develops it reaches a plateau and is not exacerbated by extended periods of fat feeding.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, consistent with our hypothesis, we show that an increase in lipid metabolites are associated with defects in tissue insulin action, suggesting that lipotoxicity is a generalised mechanism associated with the induction of insulin resistance in individual tissues of mice. Studies in rodents [7,[19][20][21]23], dogs [24] and humans [25][26][27], have shown that short-term exposure to HFD/overfeeding (3-28 days) results in the rapid development of insulin resistance and glucose intolerance. Often these changes occur with only modest increases in fat mass, highlighting that metabolic defects occur prior to the onset of obesity and do not require extensive periods of fat feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2005). As in genetic models of type‐2 diabetes ( ob/ob and db/db mice), PPAR α activation and related changes in expression levels of PPAR α targets such as PDK4 or MCAD appear only after 5 weeks (Buchanan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin signaling mediated by activation of eNOS in hearts such as increasing the carbohydrate oxidation during ischemia and direct activation of AKT have shown antiapoptotic function and cardiac protecting effect [69]. Insulin resistance is caused due to the improper metabolism of lipid in heart which leads to the improper management of insulin and decreases cardiac ef iciency in cardiomyocytes [30,[70][71][72][73].…”
Section: Lipid-induced Defective Insulin Signalingmentioning
confidence: 99%